Carbon copy - Shapiro, Stanley; Schultz, Michael; DeHaven, Carter (Sta. Monica, California MGM Home Entertainment, 1981)
Like father, unlike son!George Segal, Susan Saint James and two-time Ocar®winner* Denzel Washington star in this "zany" and wickedly funny comedy that strikes a brilliant "balance between broad humor and genuinely poignant moments. When straight-laced executive Walter Whitney (Segal) discovers he has a long-lost black son (Washington), he attempts to adopt him into his uptight family-only to watch his tidy world go hopelessly and hilariously awry. But after losing his job, his home and finally his cool, Walter slowly begins to see that all he really needs is a little bit of courage...because when it comes to family, happiness id never black and white.
Executive producer, John Daly
George Segal, Susan Saint James, Jack Warden, Denzel Washington.
Dolby digital.
In English with French & Spanish subtitle.
Keywords: Comedy films